A Combination Therapy Consisting of Teicoplanin for Febrile Neutropenia in Pediatric Patients with Malignancy - FUJISAKI, Hiroyuki; HASHII, Yoshiko; KUSUKI, Shigenori; KIM, Ji Yoo; HARA, Junichi; OKADA, Keiko; TOKIMASA, Sadao (The Japanese Journal of Pediatric Hematology, 2006)
We examined the efficacy and safety of teicoplanin for the second-line therapy of malignant febrile neutropenia in pediatric patients. Ten patients, in which carbapenem-based empirical therapy was ineffective, were treated with teicoplanin-based second-line therapy. The teicoplanin dosage regimen was 10 mg/kg every 12 hr for three or seven doses, then every 24 hr. Concomitant antibiotics were fourth-generation cephalosporin or carbapenem. Treatments were effective in five patients and an improvement of symptoms was seen in three patients. There was no severe adverse event, and nine patients achieved efficacy and safety concentrations. Therefore, the monitoring of concentrations did not seem to be necessary. However, in order to ascertain that appropriate concentrations are been achieved, trough concentrations should be measured when teicoplanin is ineffective. We conclude that teicoplanin isuseful for second-line therapy of febrile neutropenia in pediatric patients.